Peningkatan Pengetahuan Ultra Processed Food pada Kader Remaja di Rumah Susun Sederhana (RUSUNAWA) Kotamadya Jakarta Utara - Fathurrohmah Isnadia Siwi; Nicky Febrilian; Laras Sitoayu; Juwita Putri Dian; Zebua Zebua; Kania Putri Khaerunnisa; Wina Putri Nadiyah (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2026)
Adolescence is a crucial period that requires special attention regarding nutritional intake, given that adolescents often make inappropriate food choices. Ultra-Processed Food (UPF) is a popular choice among adolescents, despite its generally low nutritional value. Regular consumption of UPF can disrupt appetite regulation, lead to excessive Jakarta intake, and contribute to weight gain and the risk of obesity. Several studies also suggest that UPF consumption patterns can trigger insulin resistance, systemic inflammation, and changes in the gut microbiota. To address this issue, the “Adolescent Nutrition Education: Ultra-Processed Food” intervention was conducted at the Marunda Flats (Rusunawa), North Jakarta. This intervention used an interactive lecture method supported by multimedia presentation media. The activity began with a pre-test, material delivery, a question-and-answer session, and concluded with a post-test. Evaluation results showed an increase in participants’ knowledge after participating in the intervention, as indicated by an increase in the average post-test score from 77 to 87. This indicates that education using the interactive lecture method combined with PowerPoint Presentation (PPT) media and 3D AR posters is effective in increasing adolescents’ understanding of the dangers of consuming Ultra Processed Food. Furthermore, this activity has successfully raised awareness among teenagers about making wiser food choices and reducing their consumption of packaged foods, which pose health risks, such as obesity and metabolic diseases. It is hoped that these youth cadres can become agents of change in their communities by disseminating the knowledge they have gained to their peers and the surrounding community.